Safety profiling of pioglitazone and telmisartan combination by sub-chronic toxicity study in rat - Sengupta, Pinaki; Das, Arindam; Ibrahim, Fuzianna; Mandal, Uttam Kumar; Chatterjee, Bappaditya; , Syed Mahmood; Das, Sreemoy Kanti; Kifayatullah, Muhammad (Elsevier, 2016)
It has been reported that the major cause of mortality in diabetes is cardiovascular diseases and contribution of hypertension is significant in this context. Pioglitazone, a thiazolidinedione class of therapeutic agent is used to treat type 2 diabetes mellitus. Telmisartan, an angiotensin receptor blocker antihypertensive has been reported to have beneficial effect if co-administered with pioglitazone for the management of diabetes complications. The present research work aims to evaluate the safety/toxicity profile of this combination in rat model. The investigation was carried out after co-administering the drugs to the rats for 28 days at three dose levels of 50, 100 and 150 mg/kg covering low to high dose ranges. Various hematological and biochemical parameters were studied in addition to the histopathology of the major organs in order to evaluate the toxicity profile of the combination. Absence of mortality and histopathological changes as well as unaltered hematological and biochemical parameters was observed. This preliminary investigation concludes that the combination of pioglitazone and telmisartan can primarily be stated as safe in animals, even at the dose level which is several folds higher than the intended human dose. Thus, this combination can be explored in future to develop a rational therapy regimen to treat hypertensive diabetic patients.